omicR: A tool to facilitate BLASTn alignments for sequence data - Berenice Talamantes-Becerra; Jason Carling; Arthur Georges (SoftwareX, 2021)
Bioinformatics tools for the analysis of sequencing data, are becoming accessible for most scientists. Beginners who are unfamiliar to these tools can be overwhelmed when learning to handle large sequencing datasets. We announce omicR for Windows, which is a user-friendly tool with a graphical user interface that creates fastA files from sequencing data in tabular format such as genotyping-by-sequencing data. OmicR downloads genomes or other sequence sets from the NCBI web server and creates a genome database from the selected references. Subsequently, the user query sequences are aligned to the references and the alignment results are filtered, selecting the best match per sequence.